Strategic Diagnostics of the Industry as a Strategizing Object - N. I. Sasaev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The changes associated with the strengthening of existing trends, the translation of global trends to regional and national levels, the emergence of new trends and their scaling up to the world level, leads to a transformation of conditions and the emergence of new strategic factors of economic development. This non-stationary process, which declares both negative and positive aspects, complicates the monitoring, search and selection of long-term guidelines for the industrial development of the economy, which justifies the relevance of the development of the methodological apparatus for strategizing industries.The industrial strategy developed in accordance with the general theory of strategy and the methodology of strategizing, the founder of which is Foreign Member of the Russian Academy of Sciences Vladimir L. Kvint, is designed to systematize and take into account the variability of conditions, the variety of strategic factors and emerging opportunities, decompose the latter to the level of strategic priorities, the implementation of which will generate high efficiency over the entire horizon of strategizing.At the same time, the general theory of strategy is a young science, being in constant contact with practice, the theoretical foundations and methodological provisions of its main directions, including industrial, are still at the stage of formation and improvement.Making correct and reasonable strategic decisions increasingly depends on the depth of studying the object of strategizing. In this regard, the purpose of this article was to disclose one of the preparatory stages for the development of a strategy, namely, the study of the industry as an object of strategizing.The article justifies the necessity of dividing the analysis of the industry as an object of strate-gizing into two stages: strategic diagnostics (the study of the main characteristics, features, the current trajectory of development and potential), and OTSW-analysis (the study of the object of industrial strategizing from the position of searching for future prospects, choosing a vector of long-term development and forming a trajectory of movement in the chosen direction). In addition, the author indicates the potential elements of strategic diagnostics of the industry as an object of strategizing and reveals the key aspects of each of the areas of analysis.